Social Winners and Losers: A Case Study of Press Construction - Shoebridge, Andrea (University of Queensland, School of English, Media Studies & Art History, 2014)
The role of mass media in framing public discourse about gendered life courses is a fundamental mechanism for reinforcing patriarchal culture. Women who do not comply with the marriage and maternity mandate are subject to the type of personalised reaction experienced by Australia’s first female prime minister that triggered renewed public debate about misogyny in social organisation. Using case study methodology and framing analysis, I examined a feature published in the national broadsheet about marriage trends that made patriarchy’s preferred model explicit. The communication practices used in the feature are discussed in terms of ‘truth’, and how they might reflect and confirm the attitudes and beliefs of the newspaper’s readership.